Association between free T3 and sarcopenia in euthyroid older patients with Hashimoto’s thyroiditis - Chen, Jin-Liang; Gao, Yuan; Xiao, Qian (Frontiers in Endocrinology, 2025)
PurposeGrowing evidence suggests that thyroid hormones play an important role in the process of sarcopenia during aging. The aim of our study was to investigate whether thyroid hormones have an association with age-related sarcopenia in euthyroid geriatric patients with Hashimoto’s thyroiditis (HT).MethodsA total of 442 euthyroid older patients with Hashimoto’s thyroiditis were included in this cross-sectional study. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Body composition, grip strength and gait speed were assessed in participants. Concentrations of thyroid hormones were determined by immunoassays. Logistic regression analyses were carried out to assess the association between free T3 (FT3) levels and sarcopenia risk.ResultsCompared to non-sarcopenic patients, FT3 levels were found to be lower in the sarcopenic group (2.92 pg/ml vs 3.00 pg/ml, p<0.05). Multiple linear regression analysis showed a significant positive association between FT3 and hand grip strength, gait speed, skeletal muscle mass. Multivariable logistic regression analysis showed that FT3 levels were independently associated with sarcopenia (odds ratio 0.533 [95% confidence interval 0.343, 0.829], p=0.005) and low gait speed, low hand grip strength, low skeletal muscle index.ConclusionHigher FT3 levels within normal range was positively associated with skeletal muscle mass, hand grip strength and physical function in elderly euthyroid individuals with HT.